EFFECTIVENESS OF INSTUMENTAL ASSISTED SOFT TISSUE MOBILIZATION TECHNIQUE WITH STATIC STRETCHING IN SUBJECTS WITH PLANTAR FASCIITIS (International Journal of Physiotherapy, 2014)
Background: Instrumental assisted soft tissue mobilization and static stretching found to be effective in plantar fasciitis, however the combined effectiveness of these techniques were unknown. The purpose of this study is to find the effect of Instrumental assisted soft tissue mobilization technique for plantar fascia combined with static stretching of triceps surae for subjects with chronic stage of Plantar Fasciitis on pain intensity, ankle dorsiflexion range of motion and functional disability.Methods: An experimental study design, selected subjects with chronic Plantar Fasciitis randomized subjects into each Study and Control group. Total of 40 subject’s data who completed study, 20 in each group, was used for analysis. Control group received conventional exercise while Study group received conventional exercises with Instrumental assisted soft tissue mobilization combined with static stretching of triceps surae muscle. Outcome measurements such as Intensity of pain using Numerical Pain Rating Scale-101 (NPRS-101), function disability using Foot Function Index Pain Subscale (FFI) and ankle dorsiflexion active range of motion using Goniometer was measured before and after 2 weeks of intervention.Results: There is statistically significant improvement in means of NRS-101, ankle dorsiflexion active range of motion and Foot Function Index Pain Subscale after intervention in both groups. When the post-intervention means were compared between Study and Control group after 2 weeks of treatment there is statistically significant difference in means between the groups whereas study group showed greater percentage of improvement than control group.Conclusion: It is concluded that Instrumental assisted soft tissue mobilization technique combined with static stretching of triceps surae muscle is significantly effective than conventional exercises on reducing pain, improving ankle dorsiflexion range of motion and functional disability for subjects with chronic Plantar Fasciitis.